Enolase isoenzymes in the cerebrospinal fluid of patients with diseases of the nervous system. - Royds, J A (1983)
Alpha and gamma enolase isoenzymes have been studied in 212 patients with a variety of neurological diseases. The results show that these proteins are sensitive markers of tissue damage which enable a distinction to be made between the involvement of glial and neuronal components.